2021
DOI: 10.36222/ejt.893327
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Investigation of Fatigue Behaviours of Non-Patched and Patched Aluminium Pipes

Abstract: In this study, the fatigue behaviors of non-patched and patched aluminum pipes were investigated numerically. The Finite Element Method was used for fatigue analysis in the study. Finite Element Method was implemented with Ansys Workbench (15.0) program. Al 6063 type aluminum pipe, DP-460 type adhesive and [0/90]2 reinforced angled glass-epoxy composite patch material were used in the analyzes. As a result of the numerical study, it was observed that patch size is an effective parameter in fatigue strength and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Lap shear testing of the joints was performed using a Zwick Roell-Z020-UTM (German make) with a load cell of 20 kN. The tests were performed at room temperature (32°C, 80% relative humidity) with a traverse speed of 2 mm min −1 according to ASTM Type-V D-638 standard (Adin and Okumuş, 2022; American Society for Testing and Materials, 2016; Adin et al , 2021). An optical microscope, supplied by Conation Technologies Ltd., Pune, India, fitted with five mega-pixel camera was used for the macro-structure and fracture analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Lap shear testing of the joints was performed using a Zwick Roell-Z020-UTM (German make) with a load cell of 20 kN. The tests were performed at room temperature (32°C, 80% relative humidity) with a traverse speed of 2 mm min −1 according to ASTM Type-V D-638 standard (Adin and Okumuş, 2022; American Society for Testing and Materials, 2016; Adin et al , 2021). An optical microscope, supplied by Conation Technologies Ltd., Pune, India, fitted with five mega-pixel camera was used for the macro-structure and fracture analysis.…”
Section: Methodsmentioning
confidence: 99%
“…They found that patching with composites increased fatigue life significantly. Adin et al [11] worked on the effect of patching aluminum pipes on the fatigue stresses numerically. They saw that patch dimensions are important in fatigue stresses and higher fatigue stresses were obtained in quarter-circle patches.…”
Section: The Effect Of Damage Line and Patch Dimensions On Tensilementioning
confidence: 99%
“…Severe plastic deformation (SPD) processes have been utilized to produce ultra-fine grain (UFG) structures in metals and alloys including eliminating environmental pollution, low costs, producing larger samples. [8][9][10][11][12][13][14][15][16] ARB is conducted on metal or alloy sheets with cumulative rolling passes usually with 50% of thickness reduction ratio. The product results of this process showed that this process is suitable for fabricating a wide range of metal matrix composites (MMCs) reinforced with metals or ceramics in hot and cold conditions.…”
Section: Introductionmentioning
confidence: 99%